Community Empowerment Through Thematic Real Work Lectures (KKN) in Kencana Village RW 09 Bogor City - Hurriyaturrohman Hurriyaturrohman; Dea Anwariyah; Desty Anggraheni; Dewi Noor Putriandi; Muhammad Fikri Al-Farabi; Muhammad Fazri Nurjunian (LPPM UIKA Bogor, 2024)
Integrated Thematic KKN for the community is to increase public awareness by playing an active role in developing the productivity of development resources according to their facilities. The UIKA Bogor Integrated Thematic KKN activity in 2023 is one of the activities with a community development approach, where in the implementation of this activity the planning process as well as the action of community assistance programs both in social, economic, health, education, legal, and religious aspects as well as appropriate technology in an integrated manner. The KKN held in 2023 by group 52 focused on the kencana village, which is a village that is leading to an urban village with an area of ± 227.727 Hectares, located in Kecana Village, Tanah Sareal District, Bogor City. The activities carried out by group 52 are divided into three programs. The flagship program is Seedling Planting which consists of 100 plant seeds such as (teak, avocado, durian). Supporting programs include teaching English, basic introduction to computers to al Ghani students, socialization and counseling on clean and healthy living behavior, Posbindu from toddlers to the elderly. Participation programs include recitation for the men of Kencana RW 09, teaching and learning activities at the Ar Roza Foundation, and celebrating the 78th Independence Day of the Republic of Indonesia.